Activation of NO Donors in Mitochondria: Peroxidase Metabolism of (2-hydroxyamino-vinyl)-triphenyl-phosphonium by Cytochrome c Releases NO and Protects Cells Against Apoptosis - Stoyanovsky, Detcho A (2008)
In mitochondrial apoptosis, the formation of cytochrome c-cardiolipin complex ([CL-cyt c]) with peroxidase properties is an early event in the cascade of reactions that leads to cell death. Herein, we report the synthesis of a new prodrug, (2-hydroxyamino-vinyl)-triphenyl-phosphonium (HVTP), which compartmentalizes exclusively into mitochondria, undergoes a [CL-cyt c]-catalyzed bioactivation to nitric oxide (NO), inhibits peroxidase activity, and protects cells from apoptosis.